DEEP WELL WATER TREATMENT PLANNING IN KLUNGKUNG REGENCY WITH GRANULAR ACTIVATED CARBON (GAC) UNIT PROCESS - Ni Kadek Dian Utami Kartini; Nurul Baiti Listyendah Zahra; Ariyanti Sarwono; I Wayan Koko Suryawan (Politeknik Negeri Semarang, 2022)
Deep wells are one of the sources of water to meet the daily needs of the people in Klungkung Regency. The well water still contains high levels of aluminum and color. For this reason, proper processing planning is needed for the characteristics of wells in Klungkung Regency. One of the appropriate process units to use is the Granular Activated Carbon (GAC) adsorbs. The purpose of this study is to find out the details of the unit area and the need for GAC used in treating well water in Klungkung Regency. The land area required for this unit is 3.82 m2, where this area already includes 2 GAC units. The GAC requirement for each unit is 3209.4 kg with a regeneration time of 6.6 months.